Radio dla każdego. (Wejherowo : [s.n.], 1946)
Afisz inf. o możlwiości kupna radia lipiec 1946 r.
Keywords: Odbiorniki radiowe -- druki ulotne; Wejherowo (Polska) -- 1945-1970 -- druki ulotne; Wejherowo (Polska) -- 1945-1970 -- źródła